Electrical performance and economic feasibility analyses of hybrid and battery storage devices used in remote area islanded renewable energy systems - Chotia, Imran (Department of Electrical Engineering, 2017)
South Africa has the fifth largest coal based utility grid in the world, unfortunately many regions in the country are simply too remote for connection with this grid thus have no electricity access [1]. Many remote areas possess high wind speeds and solar irradiance exposure, which makes them ideal for Renewable Energy Systems (RES) but the electrical and economic viability of this deployment, is still in question. Based on these observations, an electrical performance analysis and economic feasibility study based on islanded RES deployment in remote areas of SA is conducted. RES growth is restricted to the effectiveness of its energy management strategy. Pumped Hydro Storage (PHS) is the cheapest islanded large scale storage option but its assignment is restricted to applicable an landscape and terrain [2], [3]. After conducting a critical review, the Lead Acid Battery Storage System (BSS) and Hybrid Battery Supercapacitor Storage (HBS) were over the PHS. A theory development study on established generations systems and storage models was used to compare software designs which resulted in the selection of Matlab software for electric performance analysis and HOMER for the economic feasibility study. The electric performance analysis was divided into three case studies based on the input power supply, viz. ideal voltage source, Solar Photo Voltaic (PV) and Wind Energy Conversion System (WECS), with each case being connected to a BSS and HBS. A load profile and solar and wind resource investigation was conducted using the NASA, Wind Atlas of South Africa (WASA) and Solar GIS database. Electrical cases were modelled in Matlab and evaluated in terms of power security, load matching, power response and charge algorithm accuracy. The results showed that deploying an islanded RES in South Africa is indeed electrically feasible based on the high power security, load matching accuracy, and disturbance response seen in the solar-RES cases. The wind-RES maintained an uninterruptable power supply but failed to match the load as accurately. Cases which used the HBS showed improvements in power stability; load fluctuation response and an extension of storage device lifespan when compared to the BSS connected cases. This was due to the supercapacitor high power density which made it ideal for the compensation of RES and load fluctuations. Three new cases were established for the economic study as follows; solar, wind and hybrid solar-wind generation all tested under BSS and HBS conditions once again. A socio economic study established the region of deployment, natural resources, terrain, landscape as well as the price of WECS, PV, storage, and converter components. These findings were used in HOMER to construct an optimised combination of components required for the supply of a 5MWh/d average load. This was followed by a sensitivity analysis which conducted 14 different optimisations at loads ranging from 1-10MWh/d. Economic benefits of the supercapacitor power density was uncovered through a reduction of the required RES Peak Operating Reserve (POR) capacity. This is especially significant in islanded RES, as they demand large POR in order to maintain autonomous power supply. This amounted to substantial NPC savings ranging from $1 - $7.5 million for the 25 year project. What was more interesting was the hybrid wind-solar generation results of the last case which extended total NPC savings, by up to $10 million. The hybrid-HBS does show some POR reductions which brought the COE to 0.3$/kWh on average, with the hybrid-BSS at 0.35$/kWh. The hybrid-BSS is slightly more expensive but has a reduced complexity which can be more inviting to project engineers therefore both hybrid cases are exceptionally feasible for local RES deployment. Single source RES is indeed electrically and economically feasible and shows extended sizing and performance benefits when implementing HBS. However, the cost reductions and performance benefits of hybrid generation make it the most practical solution to islanded RES in South Africa.